برِصغیر کےاُردو تفسیری ادب کا کلامی اسلوب (تحقیقی و تجزیاتی مطالعہ) (Khairulummah, 2023)
Allah is the creator of this universe and mankind. It is his habit that after the creation of mankind, He has always provided proper and complete guidance for him. In this regard, Allah Almighty started a long chain of prophets and messengers, the last link of which is the Prophet of Islam. Allah Almighty made him a leader and guide for all humanity and sent him to this world by giving him a complete code of life in the form of the Holy Qur'an. The Holy Quran is the perfect and authentic source of guidance for all mankind. This is the reason that the scholars of every time, participated in the promotion and publication of Quranic sciences in every era. Even non-Muslim scholars also spent their efforts in this good work, which resulted in the creation of many academic and literary collections related to Quranic studies. In the field of Tafsir-i-Qur'an, Muslim and non-Muslim scholars wrote Tafsirs of the Holy Qur'an adopting different methods and styles. The region of the Indian sub-continent has been very fertile in this respect where a lot of exegetical literature has been created in different languages. In this region, an important style of interpretation of the Qur'an is the KALAMI style (کلامی اسلوب), in which many scholars contributed. In this research, an attempt has been made to find out that when did this specific style begin and evolve in the commentary literature of the subcontinent? What were the reasons for this? Also, a research study has been done regarding the famous kalami(کلامی) interpretations of Urdu language and their unique styles. Through the analytical method of research, the beginning and evolution of Urdu verbal commentary literature created in the region of the Indian sub-continent, its causes and reasons, styles and its need and importance in the modern era have been evaluated in the light of which the results have been compiled.